Digital Multiliteracy-Based Anticorruption Education Model: A Framework for Innovation in Pancasila and Civic Education - Wibowo, Guntur Arie; Panda, Florentina Maria; Farikiansyah, Ilham Mahmud; Paotonan, Nesliani; Judijanto, Loso; Asparill, Teguh Ahmad (Jurnal Pendidikan Indonesia, 2024)
The country faces significant challenges related to corrupt practices, threatening various aspects of people's lives. Therefore, to overcome this problem, it is essential to instil anti-corruption principles early, especially among students who will become future leaders. This research aims to create a digital multiliteracy-based anti-corruption education model in Pancasila and Citizenship education innovation to improve students' anti-corruption attitudes. This research uses the Research and Development (R&D) method with the ADDIE development model. The research sample consisted of 36 first-semester Physical Education study program students. The results showed that the independent sample t-test result showed a significant influence between the digital multiliteracy-based anti-corruption education program and students' anti-corruption attitudes. Thus, there is an influence between each variable. In addition, this study shows that the digital multiliteracy-based anti-corruption education model successfully improves students' attitudes in fighting corruption. This study recommends integrating this program into various departments and universities to strengthen its impact. In addition, periodic evaluations are also suggested to ensure continued effectiveness.